Seroprevalence and risk factors for canine visceral leishmaniasis in the endemic area of Dias D'Ávila, State of Bahia, Brazil - Oliveira,Laura Cristina Pinho de (2010)
INTRODUCTION: Visceral leishmaniasis (VL) is an important zoonosis in relation to public health systems. Dogs are the main domestic reservoir. This study aimed to investigate occurrences of canine VL in Dias D'Ávila, State of Bahia, Brazil. METHODS: The prevalence was evaluated by means of clinical and laboratory tests on a population of 312 domestic dogs from 23 localities in this municipality, using indirect immunofluorescence and immunoenzymatic assays. RESULTS: Among the animals examined, 3.2% and 6.7% showed signs of VL, confirmed by indirect immunofluorescence and immunoenzymatic assays, respectively, with a distribution of 29.9% (24 dogs) in the rural zone and 4.9% (288 dogs) in the urban zone (p = 0.001). The clinical evaluation on seropositive dogs showed both asymptomatic animals (2.4%) and symptomatic animals (47.6%), along with other abnormalities (e.g. normocytic and normochromic anemia, with leukocytosis and thrombocytopenia). Observations relating to phenotypic characteristics (e.g. sex, age, breed and hair) did not present statistical significance, although high seropositivity among male, short-haired and mixed-breed dogs was observed. CONCLUSIONS: The findings showed that VL was a predominantly rural zoonosis and that close contact between poultry and domestic dogs significantly increased the risk of canine infection in this region.